Use of Low Dose Pregabalin for Attenuation of Hemodynamic Response to Laryngoscopy and Intubation in Treated Hypertensive Patients - Thapa, Puja; Panta, Sunita; Rayamajhi, Mallika; Khadka, Santosh; Amatya, Bishwo Ram; Shah, Ashish; Rizal, Thanesore; Kunwar, Bhuwan Raj (Nepalese Medical Journal, 2019)
Introduction: Laryngoscopy and tracheal intubation are two powerful noxious stimuli that can be potentially deleterious especially in hypertensive patients. This study evaluated the efficacy of low dose oral pregabalin used as a premedication for attenuation of this marked sympathetic response of airway instrumentation. Materials and Methods: This was a double-blind randomised study done at a tertiary level referral hospital. The trial was registered as UMIN-000037103 (https://www.umin.ac.jp/ctr/). Patients were randomly assigned into two groups. Placebo arm received multivitamin capsule and treatment arm received Cap. Pregabalin (75 mg), 60 minutes before the induction of general anesthesia. The level of preoperative sedation was assessed with the Ramsay Sedation Scale. Heart rate, systolic, diastolic and mean arterial blood pressure were monitored and recorded before and during induction, during laryngoscopy and 1, 3 and 5 minutes of intubation. Results: A total of 50 patients, 25 in each arm were enrolled. The baseline characteristics were comparable. SBP was significantly lower in the Pregabalin group than in Placebo at all the periods of recording, however, DBP and MAP decreased significantly during, after 1 and 3 minutes of laryngoscopy (p=0.001). Sedation was significantly better in the Pregabalin group with 86% in RSS 3 compared to 80% of a placebo arm in RSS2 (P <0.001). Conclusions: Premedication with a single oral dose of Pregabalin (75 mg) is effective for sedation and attenuation of hemodynamic response to direct laryngoscopy and endotracheal intubation in controlled hypertensive patients without any side effects.